On Marx's “soulless conditions” and the fate and function of religion - Wagoner, Bryan (Critical research on religion, 2013)
This review engages Berger M, Reichardt T and Städtler M (eds) (2012) Der Geist geistloser Zustände: Religionskritik und Gesellschaftstheorie. The collection, along with each of the essays, is examined as a contribution to political and social critique of religion in light of secularization and pluralization.